2017
DOI: 10.1177/1177625017713996
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptional Regulatory Role for the Membrane Type-1 Matrix Metalloproteinase in Carcinogen-Induced Inflammasome Gene Expression

Abstract: Signal-transducing functions driven by the cytoplasmic domain of membrane type-1 matrix metalloproteinase (MT1-MMP) are believed to regulate many inflammation-associated cancer cell functions including migration, proliferation, and survival. Aside from upregulation of the inflammation biomarker cyclooxygenase-2 (COX-2) expression, MT1-MMP’s role in relaying intracellular signals triggered by extracellular pro-inflammatory cues remains poorly understood. Here, we triggered inflammation in HT1080 fibrosarcoma ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…In summary, a cooperative signal transducing role for MT1-MMP was previously documented to take part in the transcriptional control of inflammasome-related genes [ 25 ], autophagy [ 24 ], and COX-2 induction [ 35 ]. Here, we now provide the first evidence for a cooperative crosstalk linking TGF-β receptor-mediated signaling to that of MT1-MMP, both activities of which have also been occurring in CSC [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, a cooperative signal transducing role for MT1-MMP was previously documented to take part in the transcriptional control of inflammasome-related genes [ 25 ], autophagy [ 24 ], and COX-2 induction [ 35 ]. Here, we now provide the first evidence for a cooperative crosstalk linking TGF-β receptor-mediated signaling to that of MT1-MMP, both activities of which have also been occurring in CSC [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among specific brain cancer biomarkers promoting invasion and metastasis and characterized by both matrix metalloproteinase (MMP) catalytic functions and intracellular signaling properties, membrane type-1 matrix metalloproteinase (MT1-MMP), a key membrane-bound MMP, is involved in extracellular matrix (ECM) degradation [ 19 , 20 , 21 ] and, more recently, signal transducing functions leading to angiogenesis [ 22 ], autophagy [ 23 , 24 ], inflammation [ 25 , 26 ], immune response [ 27 ], and cell death processes [ 28 , 29 ]. Interestingly, type I collagen, a major MT1-MMP substrate in the ECM, is a powerful inducer of cell-surface MT1-MMP expression through TGF-β–Smad signaling [ 26 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…MT1-MMP regulated the transcription of dickkopf-related protein 3 (DKK3) in urothelial cells and Smad1 in several tumor cell lines [132]. In phorbol-12-myristate-13-acetate (PMA)-stimulated HT1080 cells, the expression of MT1-MMP modulated inflammasome gene expression [134]. The transcription of IL-33 and IL-12A was MT1-MMP-dependent [134].…”
Section: Activities Of Mt1-mmpmentioning
confidence: 99%
“…In phorbol-12-myristate-13-acetate (PMA)-stimulated HT1080 cells, the expression of MT1-MMP modulated inflammasome gene expression [134]. The transcription of IL-33 and IL-12A was MT1-MMP-dependent [134]. MT1-MMP was found to translocate to the nucleus, where it induced the expression and activation of the phosphoinositide 3-kinase δ/Akt/GSK3β signaling cascade [135].…”
Section: Activities Of Mt1-mmpmentioning
confidence: 99%
“…It was shown that the silencing of MT1-MMP gene expression resulted in reduced activation of phorbol-12-myristate-13-acetate (PMA)-induced transcription factors such as ELK1, EGR1, ETS1, and ETS2, caused by dysregulation of the phosphorylation of NF-κB/p105. Similarly, mutations within the cytoplasmic domain of MT1-MMP altered RhoA/ROK expression or RhoA-dependent shedding of CD44, and changed the phosphorylation status of Erk1/2, STAT3, and Akt in various type of cancer cells (77). In addition to proteolytic functions, MT1-MMP was described to control cell migration also through non-proteolytic mechanisms.…”
Section: Membrane-type Metalloproteinasesmentioning
confidence: 99%